Behaviour of blind bolt shear connectors subjected to static and fatigue loading. (1st July 2020) - Hosseini, Seyedeh Maryam; Mamun, Mohammad Shafiqul; Mirza, Olivia; Mashiri, Fidelis
Highlights: The paper investigated the bolted shear connector's behaviour under static and fatigue loading. Stiffness, ultimate strength and ductility of welded stud and blind bolt were investigated. The experimental results used to understand S-N curve that link to the fatigue life of blind bolt. Fatigue strength of the bolted shear connectors compared with design equations of the headed stud. Fatigue failure of bolted shear connector and the local failure of concrete were studied in detail. Abstract: This paper focusses on the performance of bolted shear connectors embedded in concrete slab when subjected to static and fatigue loading. The static and fatigue capacities of shear connectors between concrete slabs and steel beams are important issues, as existing composite structures experience complex loadings during their functional working life. The conventional headed stud shear connector is the most common form of shear connection in composite construction; in contrast the high strength bolts are not commonly used as shear connectors. Among different types of bolted shear connectors, the ability of blind bolt shear connectors to be attached and detached from one side of a structure resulting in faster installation and reduce the environmental cost is attractive. Therefore, in this study stiffness, ultimate strength, and ductility of blind bolt shear connector were examined through static tests. Furthermore, high-cycle fatigue tests were conducted to develop a S-N curve for the blind bolt shear connectors. In addition, failure modes of this type of shear connector were identified in detail.